The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/jmv.24672
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of enteric adenovirus genotypes 40 and 41 identified in children with acute gastroenteritis in Kolkata, India during 2013–2014

Abstract: Human enteric adenovirus (HAdV) belonging to species F is one of the most common pathogens responsible for infantile gastroenteritis worldwide. This study was initiated to estimate prevalence and types of HAdV among children below 5 years of age seeking health care facility for treatment of diarrhea in Kolkata, Eastern India. A total of 1,562 stool specimens were tested during 2013-2014 and among them, 185 (11.8%) were positive for enteric HAdV. Maximum number of positive cases were observed among children bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
40
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 46 publications
19
40
2
Order By: Relevance
“…Moreover, a phylogenetic tree of the fiber gene of all isolated AdV‐41 strains indicated that all representative strains were associated with the GTC2 hexon gene, which was similar to the findings of other studies . Fukuda et al, have reported a strain containing the hexon gene with GTC1 pattern and the fiber gene with GTC2 pattern, and have considered the strain to be a recombinant between HAdVs of the same types.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Moreover, a phylogenetic tree of the fiber gene of all isolated AdV‐41 strains indicated that all representative strains were associated with the GTC2 hexon gene, which was similar to the findings of other studies . Fukuda et al, have reported a strain containing the hexon gene with GTC1 pattern and the fiber gene with GTC2 pattern, and have considered the strain to be a recombinant between HAdVs of the same types.…”
Section: Discussionsupporting
confidence: 83%
“…In this study, the phylogenetic analysis and amino acid identity of the hexon HVRs of the isolated type 41 strains indicated the presence of GTC1 pattern, which was closely similar to the D1 and D28 strains. The genome type D1 as a prototype strain (Tak) had been firstly described by Van der Avoort et al, in the Netherland in 1989, although it has also been reported in several other countries . Our finding suggests that the isolated strains in Iran are similar to the worldwide AdV‐41, strains D1, and D28.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In summary, we demonstrate that young children were more likely to be infected with HAdV and that co-infections with other viral pathogens are common, as previously found [28], which suggest a possible underestimation of the real HAdV burden. Our study also shows the diversity of HAdV circulating in Denmark and the possible existence of clusters of transmission.…”
Section: Discussionsupporting
confidence: 76%
“…AdV type 40 and 41 have been identified as etiological agents of gastroenteritis and are commonly detected in wastewater [7,8]. These viruses are members of the Mastadenovirus genus of the Adenoviridae family, containing a double-stranded DNA genome [6].…”
Section: Introductionmentioning
confidence: 99%